Análise da viabilidade técnica e econômica da integração do processo de recuperação de etanol por arraste (stripping) com CO2 na indústria sucroenergética - Souza, Fabricio Menezes de (2021)
Brazil is the world's largest sugarcane ethanol producer which puts the country in a stand-out position among the bioenergy producers. Ethanol is an important biofuel in the renewable energy matrix. In 2017, the Brazilian Government launched the National Biofuel Policy, named “RenovaBio”. With this program, it is expected an increase in production process efficiency and a reduction in the by-product generated. To achieve these goals, producing a more concentrated wine in the fermentation stage is a good strategy. However, in the fermentation process, ethanol itself is a limiter, since it is a toxic compound to the yeasts, which reduces or even stops the cell growth rate when high concentrations are achieved. To overcome this problem, ethanol can be produced and removed from the fermentation medium as it is formed. Thus, the objective of this work was to analyze ethanol removal from the fermentation broth using the carbon dioxide striping technique. The ethanol removed by the carbon dioxide stream is recovered by absorption using monoethylene glycol. This integrated process (removal and recovery process) was implemented and evaluated in an industrial autonomous and annex distillery implemented in the Aspen Plus process simulator. The implementation of extractive fermentation in the conventional ethanol production process increased the electric energy production by 9.4% besides reduced the amount of vinasse by 0.5 liters per liter of ethanol compared to the conventional autonomous distillery. Furthermore, the sugar recovery as ethanol was increased by 1.07%. These results showed that extractive fermentation becomes economically feasible when low specific stripping gas flow rates are used in the process. However, the recovery of the entrained ethanol and the requirement of the energy to compress the carbon dioxide stream were the main factors that impact the process viability. The first one had a positive impact whereas the second one exhibit a negative impact.